Clinical efficacy of Osteoking in knee osteoarthritis therapy: a prospective, multicenter, non-randomized controlled study in China - Zhou, Jun; Zheng, Zelu; Luo, Yuxin; Dong, Yawei; Yan, Yan; Zhang, Yi; Tang, Kaiqiang; Quan, Rui; Lin, Jiaming; Zhang, Kuayue; Dong, Pengxuan; Wang, Rongtian; et al. (Frontiers in Pharmacology, 2024)
Background Osteoking has been extensively used for the treatment of knee osteoarthritis (KOA). However, it is lack of high-quality evidence on the clinical efficacy of Osteoking against KOA and the comparison with that of nonsteroidal anti-inflammatory drugs (NSAIDs). Aims To evaluate the efficacy and safety of Osteoking in treating KOA. Methods In the current study, a total of 501 subjects were recruited from 20 medical centers, and were divided into the Osteoking treatment group (n = 428) and the NSAIDs treatment group (n = 73). The Propensity Score Matching method was used to balance baseline data of different groups. Then, the therapeutic effects of Osteoking and NSAIDs against KOA were evaluated using VAS score, WOMAC score, EQ-5D-3L and EQ-VAS, while the safety of the two treatment were both assessed based on dry mouth, dizziness, diarrhea, etc. Results After 8 weeks of treatment, the Osteoking group was compared with the NSAIDs group, the VAS score [2.00 (1.00, 3.00) vs. 3.00 (2.00, 4.00)], WOMAC pain score [10.00 (8.00, 13.00) vs. 11.00 (8.00, 16.00) ], WOMAC physical function score [32.00 (23.00, 39.00) vs. 39.07 ± 16.45], WOMAC total score [44.00 (31.00, 55.00) vs. 53.31 ± 22.47) ], EQ-5D-3L score [0.91 (0.73, 0.91) vs. 0.73 (0.63, 0.83) ] and EQ-VAS score [80.00 (79.00, 90.00) vs. 80.00 (70.00, 84.00) ] were improved by the treatment of Osteoking for 8 weeks more effectively than that by the treatment of NSAIDs. After 8 weeks of treatment with Osteoking, the VAS scores of KOA patients with the treatment of Osteoking for 8 weeks were reduced from 6.00 (5.00, 7.00) to 2.00 (1.00, 3.00) (p < 0.05), which was better than those with the treatment of NSAIDs starting from 2 weeks during this clinical observation. Importantly, further subgroup analysis revealed that the treatment of Osteoking was more suitable for alleviating various clinical symptoms of KOA patients over 65 years old, with female, KL II-III grade and VAS 4-7 scores, while the clinical efficacy of NSAIDs was better in KOA patients under 65 years old and with VAS 8–10 scores. Of note, there were no differences in adverse events and adverse reactions between the treatment groups of the two drugs. Conclusion Osteoking may exert a satisfying efficacy in relieving joint pain and improving life quality of KOA patients without any adverse reactions, especially for patients with KL II-III grades and VAS 4–7 scores. Clinical Trial Registration: https://www.chictr.org.cn/showproj.html?proj=55387, Identifier ChiCTR2000034475